P493 Late and atypical presentation of mecp2 mutation. (June 2019) - Kelleher, Karen; Lynch, Sally Ann; Lynch, Bryan
Abstract : Introduction: Rett syndrome (RS) is an X-linked dominant neurodevelopmental disorder affecting girls, most commonly caused by MECP2 loss-of-function mutations. The typical phenotype of RS is characterised by a period of developmental stagnation in late infancy, followed by progressive dementia, developmental regression, stereotyped hand-movements, microcephaly and gait dyspraxia. There are well recognised variants such as Atypical Rett syndrome(Angelman-like), Zappella-variant(preserved speech variant), and Congenital Rett syndrome. Objective: We describe two cases of unrelated Irish females who presented towards the end of their first decade with unusual Rett phenotypes. Results: Both cases had normal early development. Mild/moderate developmental abnormalities were picked up at 2 years. Prior to onset of epilepsy, both cases were in mainstream school with a special needs assistant and had upright and independent gait. Case 1 developed severe progressive scoliosis from preschool age. Case 1 and Case 2 presented with severe, refractory epilepsy aged 10 and 9 respectively; consisting of a mixture of atonic and complex-partial seizures evolving to include epileptic-spasms with epileptic-encephalopathy in both. In both cases gait deterioration began as an increasingly crouched posture and shuffling gait progressing to wheelchair-dependence. Concurrently, was a profound regression in motor skills, cognitive abilities, very poor appetite and weight loss. Neither had features of hand-wringing or microcephaly. Case 1 was notable for excessive drowsiness and development of progressive neuromuscular muscle weakness leading to frequent pneumonias, life-threatening choking episodes and a progressive deterioration in her respiratory function. She died, aged 13 years, of respiratory failure. Case 2, aged 13, does not have features of progressive bulbar palsy described in Case 1. Extensive workup was unrevealing except for de-novo heterozygous mutations in their MECP2 genes. In Case 1, a novel variant of MECP2 was detected: A duplication of the majority of the protein-coding portion of exon 4. Isolated duplication of large sections exon 4 has never, to our knowledge, been described before. In Case 2 there was a deletion and seven base pair insertion in exon 4:1006_1275delinsBATGCCC(p.Leu336Aspfs*12), predicted to introduce a premature termination codon. Conclusions: Case 1 represents a unique case of MECP2 mutation, expanding our knowledge of the deleterious mutations leading to a Rett phenotype. We suggest that young girls with late onset developmental regression, new onset refractory epilepsy and crouching gait be investigated for MECP2 gene mutations. Early onset of scoliosis in an ambulatory child, and severe neuromuscular weakness are not previously known features of this condition.